Menggagas Kemitraan Multi Stakeholder dalam Pengabdian Masyarakat oleh Perguruan Tinggi - Okke Rosmaladewi (LPPM UNINUS, 2013)
Empirically, the number of poor families especially in rural areas continues to grow each year as well as the purchasing power of most people is declining. This reason is because the majority of implemented community development programs were partial, unbuildable system, and inappropriate in conformity with developed program for community needs. Higher education as a center of innovation should be responsive to the problems that occur in surrounding communities. Because the functions as listed in the Higher Education Act No. 12 of 2012 is to develop innovative, responsive, creative, skillful, competitive, and cooperative academicians through the three responsibilities in the form of research and community service. Multi-Stakeholder Partnerships between universities (Academics), companies (Business), Government and the community is one alternative in community empowerment. The partnership of those various agencies is expected to overcome the social and environmental issues which are now considered increasingly complex and secluded. Basic principles in conducting partnership is fairness, transparency, accountability, trust, and equality between the related partners. Multistakeholder partnerships in community development has a distinctive destination, where output is expected not only to have economic value (tangible benefit ) but also to have non-economic benefits (intangible benefits) particularly in developing knowledge, skills and attitudes of the target communities so they are determined and able to improve the quality of life.